Cascaded boost buck converter for solar power driven stand-alone PMSM drive. (December 2020) - Dubey, Menka; Sharma, Shailendra Kumar; Saxena, Rakesh
Highlights: Solar power driven PMSM drive employing boost-buck converter is proposed first time for a refrigeration system. Proposed system offers high efficiency over wide input and output voltage range as well as it increases life of compressor. Due to presence of inductors at the DC and AC section of the cascaded boost buck converter, very less ripple in currents are obtained at PV supply terminals and DC bus of VSI. It helps in improving efficiency and therefore low implementation cost due to reduced panel size. More flexibility in design and control approach comparative to single switch topology. Abstract : This paper deals with the boost-buck converter employed solar power based PMSM (Permanent Magnet Synchronous Motor) drive for variable speed compressor of a refrigeration system. A cascaded boost-buck converter is used as a non-inverting DC-DC converter in between solar PV panel and the PMSM drive. An independent control scheme for cascaded boost-buck converter is used to achieve non-inverting output DC bus voltage with maximum power tracking. It allows variable voltage control at PV panel with reduced voltage stress across the boost-buck converter switches under a desired voltage gain and system efficiency. The ZDC (Zero Direct Current) based vector-oriented control is employed for the VSI (Voltage Source Inverter) for speed control of non-salient pole PMSM drive. A DSC (Digital Signal Controller) dSPACE 1104 is used for real time validation. Simulation results are obtained to validate the performance of proposed control algorithms and test results are obtained with a rooftop solar PV panel.